Theoretical Aspects of the Design of Fund-Supported Adjustment Programs. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1987)
This paper was originally prepared for a seminar of the Executive Board of the Fund. In the seminar, Executive Directors expressed a broad range of views with regard to both the adequacy of the Fund's approach to financial programming and the validity of the analysis presented in this paper.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet